Determinants and Welfare Impacts of Mobile Internet Adoption in African Countries - Rodriguez-Castelan, Carlos (The World Bank, 2022)
Digital technologies (DTs) are becoming an important mechanism for unleashing inclusive development, particularly across Africa. The rollout of mobile broadband internet (3G) coverage has expanded substantially in several African countries; however, digital divides persist across various groups. The issue of affordability - the combination of low household consumption and the high prices of services - is a main constraint on internet adoption across Africa. Evidence in case studies on Nigeria and Tanzania reveals that greater 3G coverage is associated significantly with higher household consumption, lower poverty rates, and positive labor market outcomes. Policies focusing on reducing household budget constraints, the price of mobile data, and increasing competition in service provision are critical to supporting the expansion of internet access
Keywords: Affordability; ICT Economics; Information and Communication Technologies